Maharashtra State Development Report - Planning Commission (Planning Commission, 2007)
India is a land of diversity, both in terms of natural and man-made systems. In order to alleviate poverty and improve the quality of life of its people, the country needs an accelerated process of development. However, it is imperative that this development process be economically feasible, socially equitable and environmentally sustainable. There are several inter-state and intra-state disparities with regard to development and poverty. These regional imbalances call for the region specific development strategy and policies.
Planning Commission Government of India
Planning Commission Government of India